The Construction of Accounting Meaning in the Preparation of Financial Statements Based on SAK EMKM Among MSME Operators at Sukawati Market: A Phenomenological Study - Wayan Tari Indra Putri Putri; Wayan Eny Mariani; Ni Nengah Lasmini (Journal of Creative Power and Ambition (JCPA), 2026)
The practice of preparing financial statements based on SAK EMKM among MSME entrepreneurs is often viewed as a technical administrative issue, whereas in the context of traditional markets, this practice is closely tied to the social and cultural experiences of business owners. This study aims to understand the construction of accounting meaning among MSME entrepreneurs at Sukawati Market in Bali. The study employs a phenomenological approach using purposive sampling of 5 active MSME entrepreneurs. Data were collected through in-depth interviews, participatory observation, and document analysis, and were subsequently analyzed using phenomenological thematic analysis. The results revealed four main themes: accounting as a tool for survival; SAK EMKM as an administrative formality; the influence of culture and family relationships on financial management; and financial statements as a symbol of business professionalism. These findings indicate that MSME accounting practices are not neutral but are shaped by life experiences, local culture, and social dynamics. This study contributes to strengthening the interpretive perspective in accounting and provides implications for the development of MSME mentoring based on local cultural contexts.